AKTIVITAS KOMUNIKASI PADA RITUAL KEAGAMAAN (STUDI ETNOGRAFI KOMUNIKASI DALAM RITUAL TUMPEK WARIGA DI BALI) - Putu Feby Sukma Yanti; Iis Kurnia Nurhayati (Dialektika, 2018)
Indonesia consists of various provinces, regions, tribes, and customs with cultural diversity. One of famous region in Indonesia which is the best known for its culture is Bali. The cultures could be in form of sacred ritual as the special honor either for the human beings themselves or the environments, started from the human life cycle to the environmental cycle. Tumpek Wariga as one of sacred ritual in Bali is conducted as human gratitude and thanks to the Almighty God for all the plants which have given prosperity and welfare for human life. The interesting thing from Tumpek Wariga ritual is that in this globalization era, when people grows more selfish and ignores the environment and culture around them, evidently there are still people who hold their cultural about environment conservation principle and their religious responsibilities. This research uses qualitative method with ethnography communication studies, and also with constructivism paradigm. The data was collected through partisipants observation, depth interview and literature review. This research is intended to explain the communication activity on Tumpek Wariga ritual in Bali through diskrit units those are communicative situation, communicative events and communicative acts. Based on the result of the research, the conclusion is that the communicative situation on Tumpek Wariga ritual was really peaceful, quite, sacred, full of Hindu culture and tradition and full of hope. Communicative events are reflected ritual procession in sequence from the start to the end. While on communicative acts showed how acts or interactions which happen through verbal, nonverbal and symbol of communication. All three elements of research results consisting of communicative situation, communicative events and communicative acts became the key in describing communication process that was found on Tumpek Wariga ritual in Bali.